Different outcomes of balloon atrial septostomy and the association of C677T polymorphism in MTHFR gene on TGA children - Salih, Aso Faeq; NazdarAmin , Banan M. (Cellular and Molecular Biology, 2022)
Balloon atrial septostomy (BAS) remains an essential palliative interventional procedure in neonates with transposition of great arteries (TGA) and restrictive inter-circulatory mixing (low saturation) that does not respond to prostaglandin E1 therapy for maintaining ductal patency. The short- and intermediate-term outcomes of BAS were evaluated in patients with TGA, and the association of C677T polymorphism in the MTHFR gene was considered on these patients at Solemani Center for Heart Diseases, Dr. Jamal Ahmad Rasheed Pediatric Teaching Hospital, and Shar Hospital in Sulaymaniyah city. For this purpose, a retrospective study was used to evaluate short- and intermediate-term outcomes of BAS in 65 consecutive neonates who have been diagnosed with TGA and restrictive inter-circulatory mixing using echocardiography in three leading hospitals in Sulaymaniyah city, during the study period from June 2011 until January 2020. Also, for genetic polymorphism assessments, in addition to 65 patients, 65 healthy children were included in the study. 2ml of intravenous blood was collected and genomic DNA was purified from peripheral blood using the Blood genomic DNA extraction kit (Life Science, USA). PCR-RFLP method was used to determine the genotype of the subjects. All 65 of the neonates diagnosed with TGA were included in this study; 61 of the cases underwent the Rashkind procedure at a median age of 15 days, and four of the neonates died before the process. Prostaglandin E1 infusion was implemented on five of the cases before the procedure, three of whom remained hypoxic. All procedures were performed successfully under the echocardiography guide, but in 26 cases, the process was conducted with the aid of fluoroscopy with an improvement of mean SPO2 (52.59% ±7.84 to 86.57% ±3.39). An excellent short-term outcome was seen in 85.2% of the cases. Forty-three of the cases underwent the operation at the median age of six months. At the median age of 32 months, 60.7% of the cases had a good outcome on the follow-up. The results also showed a significant difference between the two groups in genotypes and alleles (P<0.05). This result confirms the relationship between C667T polymorphism of the MTHFR gene and transposition of great arteries disease. BAS is an effective palliative procedure in neonates with dextro-transposition of the great arteries (d-TGA) and can be safely performed at the bedside using echocardiography. It has an excellent short-term outcome and has a relatively good intermediate-term effect, but this depends on the later performed correction operation.